2018
DOI: 10.15430/jcp.2018.23.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Source of Information About Early Detection Techniques of Breast Cancer Among Women in Iran: A Systematic Review

Abstract: BackgroundAn increase of access to knowledge about early detection techniques of breast cancer can reduce this mortality rate. This study aimed to determine the knowledge and source of information about early detection techniques of breast cancer among Iranian women.MethodsBoth International (PubMed, Web of Science, and Google Scholar) and national (scientific information database [SID] and Magiran) databases were reviewed launching to September, 2017 to obtain related articles. Steps involving the screening, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
(23 reference statements)
0
13
1
Order By: Relevance
“…However, in Hassanzadeh's study, women's knowledge was at a desirable level, though they had a poor practice in this field (18). The results of a meta-analysis by Ahmadi in Iran showed that women's awareness of BC screening in various studies was between 5 and 79.8% (22). Considering the findings of the present study and some contradictory results of other studies in Iran, it seems that there is no coherent plan to involve women in the BC screening program.…”
Section: Discussioncontrasting
confidence: 73%
“…However, in Hassanzadeh's study, women's knowledge was at a desirable level, though they had a poor practice in this field (18). The results of a meta-analysis by Ahmadi in Iran showed that women's awareness of BC screening in various studies was between 5 and 79.8% (22). Considering the findings of the present study and some contradictory results of other studies in Iran, it seems that there is no coherent plan to involve women in the BC screening program.…”
Section: Discussioncontrasting
confidence: 73%
“…9 BSE carried out once every month, between the 7th and 10th day of the menstrual cycle, significantly increases the chances of detecting breast cancer at the early stages when there is low risk of spread and ensures better treatment outcomes. 10 Despite this, some research on BSE indicates that women in developing countries do not perform BSE for a number of reasons which include limited knowledge of the disease and a lack of skill to perform the exercise. 4,8,[11][12][13] Most respondents in studies undertaken did indicate that they had no idea on what to look for during a BSE and that alone reduced their interest in continuing the exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Its peak incidence age in Iranian women is in the 4 th and 5 th decades of life, which is a decade younger than the global peak age of incidence [4] . Furthermore, this deadly disease can be cured by early detection and timely treatment [ 5] and the incidence and mortality rates can be reduced through prevention and screening [6] . The most efficient method for the early detection of this disease is screening.…”
Section: Introductionmentioning
confidence: 99%
“…However, they are not yet taken seriously by most doctors as well as by women in most medical centers in developing countries [9] . Various studies have shown BSE and mammography rates of 4% to 20% and 3% to 6.5% for Iran, respectively [1,6,10] . They have also reported rates of 24% and 17% for Nigeria and Malaysia, respectively [11,12] .…”
Section: Introductionmentioning
confidence: 99%